Associations between biopsychosocial factors and chronic upper limb pain among slaughterhouse workers: cross sectional study. Issue 1 (December 2016) - Sundstrup, Emil; Jakobsen, Markus; Brandt, Mikkel; Jay, Kenneth; Aagaard, Per; Andersen, Lars
Abstract Background Knowledge of factors associated with chronic pain is necessary for preventive strategies. The present study investigates biopsychosocial differences, with specific focus on rate of force development (RFD) and work ability, between workers with and without chronic upper limb pain. Methods Eighty-two male slaughterhouse workers, 49 with chronic upper limb pain and 33 pain-free controls participated in the study. Maximal muscle strength, RFD, and muscle activity was determined from fast and forceful maximal voluntary contractions for the shoulder and hand. Participants filled out a questionnaire on work ability (work ability index), work disability (Work module of DASH questionnaire), fear avoidance, and self-rated health. Additionally, pressure pain threshold (PPT) was measured in muscles of the arm, shoulder and lower leg. Results Muscle strength and RFD (determined within time intervals of 30, 50, 100, and 200 ms relative to onset of contraction) was 28 % and 58–78 % lower, respectively, in workers with chronic pain compared with pain-free controls, and paralleled by reduced muscle activity (allp < 0.001). Workers with chronic pain had lower PPT of the arm, shoulder and lower leg (p < 0.01), and reported impaired work ability index score and general health along with higher work disability and fear avoidance compared with controls (allp < 0.0001). No differences were observed between the groups in regard to age, BMI, physical activity level, job position and duration of slaughterhouse work (allp > 0.4). Conclusions Chronic upper limb pain was paralleled by reduced neuromuscular function of the shoulder and hand along with impaired work ability, work disability and general health. Future studies on chronic pain management at the workplace should carefully consider the biopsychosocial nature of pain when designing and implementing preventive strategies.